The answer to the equation: 5(x + 3)=7(x – 5) is to rewrite the equation as 5x + 15=7x – 35 and then adding like variables: 50=2x and then solving for x which is x=25.

Added 11/13/2011 8:17:41 PM

This answer has been confirmed as correct and helpful.

Weegy: Sorry can't show the graph. But here are the values. x=1, y= 1/ x=2, y=5. User: Graph the equation 4x – 5 = 2x – y User: 4x – 5 = 2x – y Weegy: 5/2x+1/4x=7/4+x SOLUTION:
5/2x+1/4x-x=7/4 >>
(5/2+1/4-1)x=7/4 >>
(7/4)x=7/4 >>
x=(7/4)/(7/4) >>
x=1 User: graph 4x – 5 = 2x – y Weegy: Sorry but I cannot graph that equation since we don't have a tool to attach a file on our answers (More)

There are no comments.